Robust superhydrophobic ceramic fiber braid for oil water separation. Issue 7 (1st April 2023) - Dong, Binbin; Lv, Yajun; Zhi, Zhenzhen; Yang, Junrui; Hu, Qiubo; Wang, Li; Abadikhah, Hamidreza; Xu, Xin; Wang, Gang; Min, Zhiyu; Zhang, Rui
Abstract: Oil-water separation by gravity has been introduced as an effective water purification technique. However, traditional materials such as metal mesh and polymer braid are challenging to utilize in harsh water environments. In this work, ceramic fiber braids with excellent chemical and thermal stability were fabricated and used for oil-water separation. Needle-like mullite whiskers with length of ∼100 nm was in-situ grown on the surface of the fibers using gas phase reaction which could significantly increase the surface roughness of ceramic fibers. The ceramic fiber was successfully converted to hydrophobic structure with water contact angle of 159.4° ± 1.9° and sliding angle of 8.8° ± 2.0°. The excellent structural stability and oil water separation performance confirm the wide range applications of the hydrophobic ceramic fiber braids in harsh water environments. Graphical abstract: Image 1